Cfd analysis of flow across cylinders with protruded surfaces using large-eddy simulations (les) - Tang, Joel Jing Ru (2017)
A numerical investigation of flow across cylinders with protruded surface placed in tandem using Large Eddy Simulation (LES). A comparison of varying distance between the two cylinders in tandem were carried out and their lift and drag forces are studied. The protruded surface of the cylinder delays the vortex shedding in the wake of the flow. This study reveals the effect of the alternating forces created by the vortex shedding on structures that are located at the wake of the flow. Such investigations are useful as it is common for cylinder structures to be placed in tandem among one another, like chimneys and lamp posts. Flow field pattern and force coefficients will be analysed and theses could be proved useful for applications for cylindrical structures in civil engineering. It is discovered that cylinders with lesser distance between them experience lower drag force and lower fatigue cycle, but creates a more erratic flow pattern in the downstream of the flow.